Attributional retraining: Promoting psychological wellbeing in older adults with compromised health - Patti C. Parker; Judith G. Chipperfield; Jeremy M. Hamm; Raymond P. Perry; Masha V. Krylova; Loring M. Chuchmach; Steve Hladkyj (Frontiers Media S.A., 2022)
Older adults make up the largest portion of the population of physically inactive individuals. Health challenges, and psychological barriers (e.g., maladaptive causal attributions), contribute to reduced activity engagement and low perceived control. This pilot study tested an attributional retraining (AR) intervention designed to increase control-related outcomes in a physical activity context for older adults with compromised health. Using a randomized treatment design, we examined treatment effects on a sample of older adults attending a day hospital (N = 37, Mage = 80). We employed ANCOVAs, controlling for age, sex, and morbidity, to assess differences in post-treatment outcomes between AR and No-AR conditions. AR recipients (vs. No-AR) reported lower post-treatment helplessness and more perceived control over their health. Our study offers evidence for AR to increase control-related outcomes and lays the groundwork for further research into supporting older adult populations with compromised health.